Selective reversal of muscle relaxation in general anesthesia: focus on sugammadex - Sorin J Brull; Mohamed Naguib (Dove Medical Press, 2009)
Sorin J Brull1, Mohamed Naguib21Department of Anesthesiology, Mayo Clinic College of Medicine, Mayo Clinic Hospital, Jacksonville, FL, USA; 2Department of Anesthesiology and Pain Medicine, The University of Texas M D Anderson Cancer Center,  Houston, TX, USAAbstract: Despite the significant improvements in the pharmacology of muscle relaxants in the past six decades, the search for the ideal muscle relaxant continues, mainly because of the incomplete efficacy and persistent side effects associated with their antagonism. Clinical concerns remain about the residual paralysis and hemodynamic side effects associated with the classic pharmacologic reversal agents, the acetylcholinesterase inhibitors. Although the development of the “ideal muscle relaxant” remains illusory, pharmacologic advancements hold promise for improved clinical care and patient safety. Recent clinical advances include the development of short-acting nondepolarizing muscle relaxant agents that have fast onset and a very rapid metabolism that allows reliable and complete recovery; and the development of selective, “designer” reversal agents that are specific for a single drug or class of drugs. This article reviews recent developments in the pharmacology of these selective reversal agents: plasma cholinesterases, cysteine, and sugammadex. Although each of the selective reversal agents is specific in its substrate, the clinical use of the combination of muscle relaxant with its specific reversal agent will allow much greater intraoperative titrating ability, decreased side effect profile, and may result in a decreased incidence of postoperative residual paralysis and improved patient safety.Keywords: selective reversal agents, cysteine, plasma cholinesterases, sugammadex